Digital Ministry and IoT: Hybrid Liturgy, Sensors, and the Presence of Faith in Cyberspace - Siregar, Dumaria (Hikmat : Jurnal Agama Kristen, 2025)
The transformation of church services into the digital realm has led to the emergence of hybrid liturgies that combine offline and cyberspace gatherings. This study designed and evaluated a privacy-by-design Internet of Things (IoT) architecture with edge processing to support pastoral decision-making based on non-intrusive participation metrics. Using a mixed-methods approach combined with Design Science Research, the study was conducted with two groups (intervention vs. comparison) over four weeks. Artifacts developed included the placement of environmental and occupancy sensors, the formulation of a Liturgical Participation Index (LIP) (vocal, kinesthetic, attentional, and communal dimensions), and a pastoral dashboard displaying only anonymized aggregates. Results showed an increase in LIP in the intervention group of Δ16 points (60→76) compared to the comparison group (Δ3 points), with the most significant increases in the vocal and communal dimensions. SUS scores were above the threshold of eligibility (≥68), and the perception of “faith presence” post-implementation was higher in the intervention group. In addition, the median CO₂lower at the intervention site, indicating greater environmental comfort and consistent with increased attention. These findings reinforce the concept of distributed sacramental presence, namely the presence of faith as heart-directed and bodily participation mediated by technology yet rooted in liturgical practice. This study recommends a phased implementation with low-risk sensors, sensor-aware liturgical cues, a streamlined dashboard, and strict consent and anonymization SOPs. Limitations include the four-week duration and aggregate sample size; further longitudinal research is recommended.